Special social groups, social factors and disparities in health and health care - Kronenfeld, Jennie J. (Bingley, U.K. : Emerald, 2016)
This volume features papers on the theme of issues in health and health care for special groups, social factors and disparities. This includes papers dealing with macro-level system issues and micro-level issues involving special groups, social factors and disparities linked to issues in health and health care. The volume also contains an examination of health and health care issues of patients and providers of care especially those related to special groups and social factors including education, family, income, government, neighborhoods, social networks, health beliefs and attitudes. This includes a focus on links to policy, population concerns and patients and providers of care as ways to meet health care needs of people both in the US and in other countries.
Special social groups and social factors / Jennie Kronenfeld -- Gun under my pillow: health consequences of the fear of assault among military women / Rose Weitz -- Barriers to health care access and utilization: a study of Native American women veterans in two Montana reservations / Luma AlMasarweh, Carol Ward -- "Your blood is sweet<U+201d>: the illness experience of Southeast Asian refugees with type 2 diabetes / Ethel Nicdao, Alixandria Henley, Jeffery Peterson -- Aboriginal health and Aboriginal education are interconnected / Angela Mashford-Pringle -- Women go and men stay home? gender and the utilization of preventive medical care among Asian and Latino adults / Bridget Gorman, Becky Wade, Alexa Solazzo -- Contextual, ecological and organizational variations in risk-adjusted COPD and asthma hospitalization rates of rural medicare beneficiaries / Thomas Wan, Yi-Ling Lin, Judith Ortiz -- The differential impact of social relationships on health outcomes for HIV positive men and women / Sara LeGrand, Teresa Scheid, Kathryn Whetten -- Pragmatism, activism, and cynicism: logics of engagement with community action to improve lesbian, gay, bisexual, and transgender (LGBT) health / Amanda Damarin, Zack Marshall, Lawrence Bryant -- Rewriting life narratives: positive coping mechanisms in adolescent mothers / Neale Chumbler, Smitha Ganashen, Colleen O'Brien Cherry, Dawn Garrett Wright, Jennifer Bute -- Does variation in the extent of individual education, and extensiveness of social security policies affect health information-seeking? / Rania Valeeva, Piet Bracke -- Reconceptualizing health lifestyles: the case of marriage / Catherine Ross, Terrence Hill, John Mirowsky -- The social stratification of job stress: how social structures create health disparity / Mark Tausig, Rudy Fenwick.
Includes bibliographical references.
Print version record
Keywords: Health & Fitness -- Health Care Issues; General practice; Personal & public health; Public health -- Social aspects